posted by Taina .
1. In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be
x + 3 = 48 => x = 45
(x + 1) = 48 => x = 47
However, at least one of these solutions fails to work when substituted back into the original equation. Why is that? Please help Eric to understand better; solve the problem yourself, and explain your reasoning.
Nuts to Eric's method. What principle of math is he using.
we can use the zero principle when
ab=0, meaning a=0 or b=0,or both =0
There is no principle which allows us to
ab=c then say either a=c or b=c